Course Correcting Power of Surveillance and Social Activism in the Heritage Restoration Process: A Case Study of Rani Pokhari, Kathmandu Metropolitan City - Shrestha, Ram; Karki, Tej (Journal of Science and Engineering, 2026)
Disasters trigger citizens’ emotions to protect lives and safeguard cultural assets. Citizens often move rapidly to support their neighbors and pay close attention to how their communities are rebuilt and how heritage is restored. This research uses content analysis to demonstrate how community surveillance and social activism play key roles in preventing heritage restoration agencies from going off track and compromising heritage values. It presents the Ranipokhari (Queen’s Pond) post-earthquake restoration case from Kathmandu Metropolitan City (KMC) to answer the research question. The findings reveal that surveillance, in concert with social activism, exposed mistakes and negligence by the pond restoration agencies, brought them back on track, and corrected temple restoration errors committed in the past.